Executive mechanisms regarding the Iraqi women's issues after 2003 (Vision for the future) - Hussein Saleh, Assistant Professor Dr. Bushra (The college of law and political science journal, 2023)
The restructuring of some official institutions or the occurrence of qualitative developments in the phenomena adopted by these institutions within the democratic transformations in Iraq after 2003, as democracy became the method of governance, and perhaps the most important outcome of this democracy is to give women’s issues and rights a major priority, as it represents the most important part of the issue of respecting human rights. So national executive mechanisms were formed to achieve a basic goal, which is to highlight the rights and issues of Iraqi women. Our research aimed to examine the reality of those national mechanisms as well as the efforts that resulted in clear and rewarding results. Or did they fail to achieve their desired outcome? With the creation of future scenes of national mechanisms that address the issues faced by Iraqi women.